2013
DOI: 10.1027/1618-3169/a000190
|View full text |Cite
|
Sign up to set email alerts
|

Is Automatic Imitation Based on Goal Coding or Movement Coding?

Abstract: A key issue for research on automatic imitation is whether it occurs primarily at the level of movements, that is, by automatically activating a representation of the movement/effector involved in the execution of the observed action, or at the level of goals, that is, by triggering a representation of the action goal, irrespective of how the motor act is physically instantiated. The present study presents two experiments aimed at investigating the contribution of movement coding and goal coding to automatic i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 36 publications
2
19
0
Order By: Relevance
“…What we actually found was that when facial movement was restricted, high empathy individuals took longer to recognize facial expressions. This too is in line with previous studies ( Strack et al , 1988 ; Chiavarino et al , 2013 ; Rychlowska et al , 2014 ), however, unexpectedly, low empathy individuals were faster in recognizing facial expression. The latter is a surprising and novel finding that to the best of our knowledge has not been reported yet.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…What we actually found was that when facial movement was restricted, high empathy individuals took longer to recognize facial expressions. This too is in line with previous studies ( Strack et al , 1988 ; Chiavarino et al , 2013 ; Rychlowska et al , 2014 ), however, unexpectedly, low empathy individuals were faster in recognizing facial expression. The latter is a surprising and novel finding that to the best of our knowledge has not been reported yet.…”
Section: Resultssupporting
confidence: 93%
“…These results also affirm our hypothesis that interfering with the imitation process of one action will significantly only affect the understanding of a related action. However, in our second hypothesis we predicted that this impairment will be more pronounced in individuals with high empathy levels compared with individuals with lower empathy levels, as found in previous studies of mimicry restriction ( Strack et al , 1988 ; Chiavarino et al , 2013 ; Rychlowska et al , 2014 ). However, what we found was that the interference was modulated by the empathy level in a way that created a dis-ordinal interaction, where the direction of the correlation of the experimental condition was reversed to the correlation of the control group (see Figure 4 ).…”
Section: Resultsmentioning
confidence: 68%
See 1 more Smart Citation
“…Furthermore, one other direct matching study has shown an effect that is opposite to what might be expected if goals are represented (i.e., a significantly smaller effect for actions that are compatible with those observed (Chiavarino, Bugiani, Grandi, & Colle, 2013).…”
Section: General Introductionmentioning
confidence: 57%
“…Although Wohlschläger and Bekkering (2002) did find an influence of goals on movements, whilst Chiavarino et al's (2013) found a counterintuitive effect of goal compatibility; i.e., a larger behavioural effect when participants' goals differed from those of a model. phenomenon with reference to a number of theoretical processes.…”
Section: Discussionmentioning
confidence: 91%